(untitled) (Ameghiniana, 2014)
Thrirty seven diatom species (Clase Bacillariophyceae) are recorded from Upper Pleistocene sediments containing mammal and bird fossil footprints impressed on an abras ion platform at Pehuen-Có, Buenos Aires Province, Argentina. These levels outcrop at the supralittoral zone of the beach. Diatoms suggest a freshwater environment rich in nutrients of a temperate climate.